Binding and docking interactions of NO, CO and O 2 in heme proteins as probed by density functional theory - Varotsis, Constantinos; Daskalakis, Vangelis (My University, 2009)
Dynamics and reactivity in heme proteins include direct and indirect interactions of the ligands/substrates like CO, NO and O 2 with the environment. Direct electrostatic interactions result from amino acid side chains in the inner cavities and/or metal coordination in the active site, whereas indirect interactions result by ligands in the same coordination sphere. Interactions play a crucial role in stabilizing transition states in catalysis or altering ligation chemistry. We have probed, by Density Functional Theory (DFT), the perturbation degree in the stretching vibrational frequencies of CO, NO and O 2 molecules in the presence of electrostatic interactions or hydrogen bonds, under conditions simulating the inner cavities. Moreover, we have studied the vibrational characteristics of the heme bound form of the CO and NO ligands by altering the chemistry of the proximal to the heme ligand. CO, NO and O 2 molecules are highly polarizable exerting vibrational shifts up to 80, 200 and 120 cm -1, respectively, compared to the non-interacting ligand. The importance of Density Functional Theory (DFT) methodology in the investigation of the heme-ligand-protein interactions is also addressed
Keywords: Density functional theory; Ligand molecules; Protein cavities; Proximal effect; Oxygen; Hydrogen bonding; Molecular dynamics; Protein binding